A comprehensive overview of exosome lncRNAs: Emerging biomarkers and potential therapeutics in gynecological cancers - Wang, Min; Fu, Lulu; Xu, Ying; Ma, Shuai; Zhang, Xueying; Zheng, Lianwen (Frontiers in Oncology, 2023)
Ovarian, endometrial, and Cervical cancer are common gynecologic malignancies (1) , and their incidence is increasing yearly (2) , with a trend toward younger patients. An exosome is a kind of tiny "teacup-like" blister that can be secreted by most cells, which is highly concentrated and easily enriched in body fluids and contains a large number of lncRNAs carrying some biological, genetic information, which can be stable for a long time and not affected by the catalytic activity of ribonuclease. Exosome lncRNA has the advantages of high efficiency and high targeting as a communication tool between cells. Detection of changes in the expression of serum exosome lncRNA in cancer patients can accurately reflect the malignant biological behavior of cancer cells (3) . Studies have shown that exosome lncRNA has broad application prospects in the early diagnosis of cancers, monitoring cancer recurrence or progression, treatment of cancers, and determining prognosis (4) . This paper reviews the role of exosome lncRNA in gynecologic cancers and related molecular mechanisms, intending to provide a reference for clinical research on the pathogenesis, diagnosis, and treatment of gynecologic malignant tumours.